The influence of periodontal treatment on serum lipid and systemic marker levels in patients with destructive periodontal disease - Kamil, Wisam Alaa; Habashnah, Rola; Hilal Abbood Al-Bayati, Lina (2011)
Objectives: Data on whether periodontal therapy affects serum lipid levels is inconclusive. The purpose of this study is to investigate the effect of nonsurgical periodontal therapy on the cholesterol levels and hs-CRP of medically healthy individuals suffering from advanced periodontitis. Methods: Following protocol review and approval by the Institutional Review Board of Jordan University of Science and Technology a total of fifty five periodontitis patients randomly distributed into either a treatment group (37 patients) who received non-surgical periodontal therapy with intensive oral hygiene instructions and a repeated course of therapy for residual bleeding in periodontal pockets or a control group (18 patients) who received delayed periodontal treatment after completion of the clinical trial evaluation. Medical history, demographic data and clinical periodontal parameters, total cholesterol, LDL, HDL, triglyceride, and C-reactive protein were collected at baseline and three months at reassessment appointments. Results: The results showed statistically significant improvements for all periodontal clinical parameters and the non-surgical periodontal therapy had no effect on the lipid parameters (P-Value=0.322, 0.540, 0.451, and 0.154 for LDL, HDL, Total Cholesterol, and Triglycerides respectively) in contrast to the significant decrease in the infl ammatory marker CRP (P-Value=0.003). Conclusions: In this study population, serum lipid levels were not associated with any improvement in periodontal heath while the destructive periodontal disease associated with increased circulating concentrations of his-CRP and the periodontal therapy reduces CRP levels.